Prenatal Exposures to Common Phthalates and Prevalent Phthalate Alternatives and Infant DNA Methylation at Birth - Petroff, Rebekah L.; Padmanabhan, Vasantha; Dolinoy, Dana C.; Watkins, Deborah J.; Ciarelli, Joseph; Haggerty, Diana; Ruden, Douglas M.; Goodrich, Jaclyn M. (Frontiers in Genetics, 2022)
Phthalates are a diverse group of chemicals used in consumer products. Because they are so widespread, exposure to these compounds is nearly unavoidable. Recently, growing scientific consensus has suggested that phthalates produce health effects in developing infants and children. These effects may be mediated through mechanisms related to the epigenome, the constellation of mitotically heritable chemical marks and small compounds that guide transcription and translation. The present study examined the relationship between prenatal, first-trimester exposure of seven phthalates and epigenetics in two pregnancy cohorts (n=262) to investigate sex-specific alterations in infant blood DNA methylation at birth (cord blood or neonatal blood spots). Prenatal exposure to several phthalates was suggestive of association with altered DNA methylation at 4 loci in males (all related to ΣDEHP) and 4 loci in females (1 related to ΣDiNP; 2 related to BBzP; and 1 related to MCPP) at a cutoff of q<0.2. Additionally, a subset of dyads (n=79) was used to interrogate the relationships between two compounds increasingly used as substitutions for common phthalates (ΣDINCH and ΣDEHTP) and cord blood DNA methylation. ΣDINCH, but not ΣDEHTP, was suggestive of association with DNA methylation (q<0.2). Together, these results demonstrate that prenatal exposure to both classically used phthalate metabolites and their newer alternatives is associated with sex-specific infant DNA methylation. Research and regulatory actions regarding this chemical class should consider the developmental health effects of these compounds and aim to avoid regrettable substitution scenarios in the present and future.